A comparative study of hospitalization costs of TKA inpatients before and after National Volume-based Procurement in Guangdong, China: an interrupted time-series analysis - Anqi Li; Gongduan Li; Dong Han; Manru Fu; Jinghui Chang; Jinghui Chang (Frontiers in Public Health)
BackgroundThis study aims to explore the impact of the National Volume-based Procurement Policy in Guangdong Province on hospitalization costs for total knee arthroplasty inpatients.MethodsInterrupted time-series analysis were used to examine the expenses associated with total knee arthroplasty for inpatients at a hospital in Guangzhou between May 10, 2021, and December 26, 2023. The period was divided into two phases based on the implementation of the policy, the pre-policy phase (May 10, 2021, to April 30, 2022) and the post-policy phase (May 1, 2022, to December 26, 2023). A total of ten indicators, derived from patients’ medical records, were analyzed. Indicators included total expenses, self-financed expenses, consumables costs, miscellaneous service fees, diagnostic fees, treatment fees, rehabilitation fees, total Chinese medicine costs, western medicine costs, and the costs of blood and blood products.ResultsA total of 1,196 valid cases were included, with 290 cases before policy implementation and 906 cases after implementation. When the implementation of procurement occurred (May 1, 2022), total expenses (β2= − 28240.17, p < 0.001), consumables costs (β2= − 31302.72, p < 0.001), and self-financed expenses (β2= − 13674.56, p<0.001) showed an instantaneous decreasing trend. The mean total expenses decreased from 65,324.73 CNY per case to 34,465.57 CNY per case, representing a reduction of 30,859.16 CNY per case. Miscellaneous service fees (β2= 440.45, p < 0.05), diagnostic fees (β2=746.00, p < 0.05), rehabilitation fees (β2=207.36, p < 0.001) exhibited an instantaneous and slight increasing trend. After implementation (from May 1, 2022 to December 26, 2023), the total expenses (β3=−106.95, p<0.05), consumables costs (β3= − 65.05, p<0.05), diagnostic fees (β3= − 22.44, p < 0.05), treatment fees (β3= − 28.01, p < 0.05), total Chinese medicine costs (β3= − 9.98, p < 0.05), and blood and blood products costs (β3= − 5.88, p<0.05) continued to decrease.ConclusionThe volume-based procurement policy in Guangdong, China has shown initial effectiveness. After it was implemented, total expenses, consumables costs, and self-financed expenses decreased. The structure of hospitalization costs also reflects the slight improvement in healthcare providers’ value and treatment planning decisions. Further attention should be given to the healthcare professionals’ labor value. The empirical analysis results provide a reference for the government further to improve the volume-based procurement for artificial joints.